TAX AVOIDANCE BERBANDING DENGAN KINERJA KEUANGAN MEMPENGARUHI CORPORATE GOVERNANCE DAN CAPITAL INTENSITY - Setiawan, Adhar Putra; Surahman, Dedy; Oktaviani, Marista (Balance Vocation Accounting Journal, 2022)
Abstract: This research is to find out tax avoidance compared to financial performance that affects corporate governance and capital intensity. Corporate governance indicators as independent variables consist of audit committee, audit quality, managerial ownership, institutional ownership and independent commissioners. The indicator of tax avoidance as the dependent variable is the Earning Tax Rate (ETR). While the indicators for financial performance as an intervening variable are Return on Assets (ROA) and Return on Equity (ROE). Research data sources can be accessed through the official website of the IDX (Indonesian Stock Exchange). The data collection technique used purposive sampling technique. The research uses SmartPLS 2.0 software to calculate the inner and outer models as well as the Sobel Test. The results of the study show that the first hypothesis is that there is no significant effect of good corporate governance on tax avoidance with the support of a positive or unidirectional influence, the second hypothesis is that there is a significant effect of capital intensity on tax avoidance with the support of a negative or unidirectional influence, the third hypothesis has a significant effect of good corporate governance on financial performance with the support of a positive or unidirectional influence, the fourth hypothesis there is no significant effect between capital intensity on financial performance with the support of a positive or unidirectional influence, the fifth hypothesis there is a significant influence between financial performance on tax avoidance with support direction of influence is negative or unidirectional.